Nanocrystalline Phase Formation inside Shear Bands of Pd-Cu-Si Metallic Glass. (14th May 2014) - Shao, Yang; Yang, Guannan; Yao, Kefu
Abstract : Pd77.5 Cu6 Si16.5 metallic glass was prepared by fluxing treatment and water quenching method. To avoid possible artifacts, shear bands were created by indentation after TEM sample preparation. Bright field image, diffraction pattern, and the dark field image of TEM that covered the shear band region were presented. A few nanocrystalline phases were noticed inside the shear bands, which favored the plastic deformation ability and supported the explanation of mechanical deformation-induced crystallization.